PENGARUH INTENSITAS MODAL, TRANSFER PRICING DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Isnaini, Rima; Asih Handayani (Jurnal Nusa Akuntansi, 2024)
Taxes are the largest source of revenue for the country, making the realization of tax revenue a crucial aspect for the growth and development of a nation. This research aims to analyse the influence of capital intensity, transfer pricing, and sales growth on tax avoidance in industrial sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The population and sample used in this research include all companies in the industrial sector. In sample selection, this research employs purposive sampling technique, consisting of 65 observational data from 13 selected companies. The data used in this study are secondary data, and a quantitative research method is applied. Tax avoidance in this research is proxied by using the cash effective tax rate (CETR). The data is processed using E-views version 12. The results of partial regression tests from this research conclude that 1) capital intensity has no significant effect on tax avoidance, 2) transfer pricing has no significant effect on tax avoidance, and 3) sales growth has a significant effect on tax avoidance. Simultaneous regression test results in this research conclude that capital intensity, transfer pricing, and sales growth collectively (simultaneously) influence tax avoidance.